Mucosal immunity and upper respiratory tract infections during a 24-week competitive season in young ice hockey players - Orysiak, J.; Witek, K.; Zembron-Lacny, A.; Morawin, B.; Malczewska-Lenczowska, J.; Sitkowski, D. (Journal of Sports Sciences, 2017)
The aim of this study was to examine upper respiratory tract infections (URTI) and their associations with resting saliva and blood immune and endocrine parameters in ice hockey players. Twenty-seven participants (age 16.5 ± 0.5 years) completed the 24-week study period. The counts/concentrations of immune and endocrine markers were compared between healthy-prone athletes (=2 episodes of URTI during the study period) and illness-prone athletes (=3 episodes of URTI) and between the URTI state (when athletes had infections) and the healthy state (the time without URTI). There were no differences in concentration/counts of saliva and blood immune and endocrine parameters between the illness-prone and illness-free athletes. Athletes had significantly lower sIgA, sIgA1 and sIgA2 concentrations (sIgA: 119.88 ± 66.88, 144.10 ± 75.0 µg/ml; sIgA1: 90.2 ± 40.64, 108.44 ± 29.8 U; sIgA2: 67.58 ± 30.1, 80.3 ± 25.61 U, respectively) and significantly higher WBC, neutrophil, monocyte and eosinophil count values and IL-1ra concentration at the time when they had symptoms of URTI than in the period without symptoms of infections. There were no differences in salivary cortisol concentration between the period of URTI symptoms and the period without URTI symptoms. In conclusion, we observed lower concentrations of salivary immunoglobulins and higher levels of blood immune parameters during URTI in athletes, which may confirm the suppression of mucosal immunity and initiation responses to pathogenic infections by innate immunity.